2017
DOI: 10.5539/gjhs.v9n7p15
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Knowledge, Attitude and Practice of Iron Deficiency Anaemia among Iron-Deficient Female Adolescents after Nutritional Educational Intervention

Abstract: Anaemia and iron deficiency are very common worldwide among female adolescents. There is a dearth of literature concerning the knowledge, attitude and practice (KAP) regarding iron deficiency anaemia (IDA). The magnitude of anaemia as a health problem is enormous and can be engaged by increasing awareness and the promotion of correct attitudes and practices. The study aims to evaluate the effectiveness of a nutrition education intervention in iron deficiency anaemia on the knowledge, attitude, and practice (KA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 17 publications
4
48
0
3
Order By: Relevance
“…The present study results indicated that the attitude of the pregnant women's toward NNJ in the study group pregnant women's was changed positively after the educational program with SSD between pre and posttest. This result was in agreement with the previous educational program done by [18,19,20,21] From the researchers' viewpoint, the educational program increased the pregnant women's' awareness about complications of NNJ; modify the misconceptions and negative traditional attitude toward NNJ manage especially illiterate women as exposure babies o sun light, give neonate certain herbs and others, and the importance of early intervention. These were important factors which change the pregnant women's attitude positively.…”
Section: Discussionsupporting
confidence: 90%
“…The present study results indicated that the attitude of the pregnant women's toward NNJ in the study group pregnant women's was changed positively after the educational program with SSD between pre and posttest. This result was in agreement with the previous educational program done by [18,19,20,21] From the researchers' viewpoint, the educational program increased the pregnant women's' awareness about complications of NNJ; modify the misconceptions and negative traditional attitude toward NNJ manage especially illiterate women as exposure babies o sun light, give neonate certain herbs and others, and the importance of early intervention. These were important factors which change the pregnant women's attitude positively.…”
Section: Discussionsupporting
confidence: 90%
“…The eight studies were summarized based on authors/year of study/country/study design, study settings/duration of intervention, target population/theory used, description of the intervention, outcome assessed/statistical significance of the outcome, effect size, and effectiveness of the intervention (Table 1). Out of the eight studies included, four were from high income countries [35,36,39,40], two from middle income countries [37,38], and two from low income countries [34,41]. Three of the studies were individual randomized controlled trials [34,36,41] and five were clustered randomized controlled trials [35,[37][38][39][40].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…So, nutritional knowledge is required for a healthy lifestyle. Improving nutritional knowledge, attitude, and practices of adolescent girls will lead to more economic growth and healthier individuals [13].…”
Section: Introductionmentioning
confidence: 99%